Effects of Trichoderma-Induced Suppressive Soil on Fusarium Wilt of Tomato - Said, Rozlianah Fitri (2005)
Twenty-two isolates of Fusarium spp. were isolated from stems and roots of tomato plants showing symptoms of foliar wilting and brown discoloration of the vascular systems. Differentiation of the isolates based on cultural and morphological characteristics had identified twelve isolates of F. oxysporum, six isolates of F. solani, two isolates of F. moniliforme, one isolate of F. chlamydosporum and one isolate of F. lateritium. However, the colonies of Fusarium oxysporum f. sp. lycopersici (FOL) appearance are not easy to distinguish from those of the non-pathogenic F. oxysporum even though they can be differentiated from other species. Species aggregates of Fusarium were further distinguished based on the DNA polymorphism. Twenty 10-mer primers were used in the initial screening of the fungal DNA and three (OPC-11, OPC-15 and OPC-18) were selected. Based on UPGMA clustering, two main clusters were defined. F. oxyspomm were grouped in Cluster I and F. solani were grouped in Cluster II. The other isolates of F. moniliforme, F. chlamydosporum and F. lateritium were distinctly isolated from these two main clusters. Pathogenicity testing was carried out on tomato cultivars Baccarat 322 and Cherry to further confirmed the differentiation between FOL and other forms of F. oxysporum. Isolate MI produced symptoms of Fusarium wilt on Baccarat 322 and Cherry, and therefore identified as Fusarium oxysporum f. sp. lycopersici (FOL). However, percentage of disease incidence was higher on Baccarat 322 variety (65.55%) compared to Cherry (29.44%). Histopathological studies of infected stems of tomato inoculated by isolate MI further confirmed the presence of fungal mass in the xylem vessels. Tomato plants with Trichodermainduced suppressive soil (UPM 40 and UPM 23) individually and as mixture (UPM 2340) gave increased in plant height, fresh weight and dry weight of leaf and root, early flower initiation and increase in yield compared to control. Disease incidence of Fusarium wilt was significantly lower at week 12 (12%) when treated with UPM 2340, followed by UPM 40 (21%), UPM 23 (29.5%) and compost alone (59.5%). Control gave the highest value of disease incidence of 100% at week 12. The experiment carried out in this study indicated that treatments with UPM 2340, UPM 40 and UPM 23 improved vigor of tomato plants and was effective in inducing suppressiveness against Fusarium wilt development, suggesting their potential role as biological control in the management of Fusarium wilt.